Upaya Diplomasi Ekonomi Indonesia di Afrika Melalui Preferential Trade Agreement Indonesia Mozambik - Larasati, Langgeng; Aseilla, Dike (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract—In recent years, Indonesia has begun to expand trade cooperation in non-traditional markets, one of which is in the African region. Indonesia is active in cooperating with Africa because Africa is the